Empire and antislavery : Spain, Cuba, and Puerto Rico, 1833-1874 - Schmidt-Nowara, Christopher, 1966-2015 (University of Pittsburgh Press, 1999)
Annotation In 1872, there were more than 300,000 slaves in Cuba and Puerto Rico. Though the Spanish government had passed a law for gradual abolition in 1870, slaveowners, particularly in Cuba, clung tenaciously to their slaves as unfree labor was at the core of the colonial economies. Moreover, the Spanish bourgeoisie was deeply implicated in colonial slavery as Spain was the last European power to abolish the slave trade and bonded labor in the Americas.
Keywords: Sociedad Abolicionista Española.; Sociedad Abolicionista Española; Antislavery movements -- Cuba.; Antislavery movements -- Puerto Rico.; Antislavery movements -- Spain.; Spain -- Colonies -- America.; Mouvements antiesclavagistes -- Cuba.; Mouvements antiesclavagistes -- Porto Rico.; Mouvements antiesclavagistes -- Espagne.; Espagne -- Colonies -- Amérique.; 15.85 history of America.; SOCIAL SCIENCE -- Slavery.; Antislavery movements; Spanish colonies; America; Cuba; Puerto Rico; Spain; Sklaverei; Abschaffung; Spanien; Slavernij.; Abolitionisme.; Esclavage -- Abolition -- Porto Rico.; Esclavage -- Abolition -- Cuba.; Kuba.; Geschichte 1833-1874.